Effects of Sintered‐Metal Cone Length on Gas‐Cyclone Classification Performance. Issue 3 (29th January 2016) - Fukasawa, Tomonori; Sunada, Satoshi; Shibata, Daiki; Yoshida, Hideto; Fukui, Kunihiro
Abstract: The gas cyclone is a classic flow device commonly used in the separation of particles from a gaseous flow stream. The gas‐cyclone classification performance is affected by the length of the porous sintered‐metal cone. Three different lengths of porous sintered‐metal cones were tested to evaluate the classification performance of a gas cyclone. Clean air was fed into the cyclone through the cone. The cone's particle cut size depended on the amount of clean air injected into the cone. In medium and long cones, a very small amount of injected clean air reduced the particle cut size, whereas in short cones, the cut size remained approximately constant and was greater than that for the traditional acrylic resin cone. In all cases, clean‐air injection reduced the powder deposition to values lower than those for acrylic resin cones. The results provide application‐based guidelines for the design and usage of sintered‐metal cones. Abstract : A cyclone's performance is determined by the efficiency in collecting particles and the inlet‐outlet pressure drop. Three types of porous sintered‐metal cones were prepared with different lengths and their classification performances were evaluated on the basis of partial separation efficiency, 50 % cut size, amount of particles deposited on the cone, and pressure loss.